Peran 3 Pilar Pariwisata Dalam Pengembangan Desa Ekowisata Pancoh - Pratama, Muhammad Surya; Usamah, Syahidan Hanry Muhammad; Husniyah, Husniyah (Kepariwisataan: Jurnal Ilmiah, 2023)
Tourism has a central role in improving the economic and social conditions of the community, where actors are able to utilize the potential of certain regions by collaborating between the government, the community, and the private sector. One of the tourism concepts that is the main destination for tourists is ecotourism which utilizes natural resources and community culture as a tourist attraction. Pancoh Ecotourism Village implements ecotourism tourism that provides a rural feel and presents community activities assisted by tourism pillars. The purpose of this research is to describe the roles of the tourism pillars involved and the strategies used in developing Pancoh Ecotourism Village. The research method used is qualitative with a descriptive approach and data collection through interviews, observation, documentation as primary data and literature study as secondary data. The results obtained in this study show that Pancoh Ecotourism Village was formed after the 2010 eruption of Mount Merapi which made the NGO TPTP Solo and the Ministry of Environment and the UGM Center for Tourism Studies directly involved to provide counseling to restore the socio-economic conditions of the Pancoh community. In its development, the Pancoh Ecotourism Village manager carried out various strategies to develop the Ecotourism Village so that it still existed in the times and was able to attract foreign and local tourists to visit. The various strategies used by the Pancoh Ecotourism Village manager are establishing cooperation with the government, the community, and the private sector which are interpreted in making tour packages, improving the quality of human resources, improving institutions, and promoting and branding through social media.Keywords: 3 Pillars of Tourism, Tourism, Pancoh Ecotourism Village